Benchmarking Study for Rubber-Based Indian Automotive Industry (Tier 1) Supply Chain: Identifying Challenges and Improving Supply Chain Management in the Rubber-Based Indian Automotive Industry (Tier 1) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present study was aimed at understanding and logically benchmarking the various factors which affect the supply chain management system in the automobile industry especially the rubber sector. The benchmarking was done so as to bring across the various factors which influence the functioning of the automobile companies, so as the areas of improvement could be brought to light. The study specifically focused on the relation of rubber sector and the supply chain, as the products from rubber sector make up significant proportion of the vehicular parts. The supply from the rubber sector was seen to come from two different categories, that is, the tyre sector and the non tyre sector. The tyre sector presents itself as an organized sector upto some extent, but still lacks the advance technologies and the research aimed towards instilling novel material and methods of tyre production. The non-tyre industry posed higher degree of challenges pertaining to its unorganized nature, primitive technology and low cost input. Hence, the benchmark associated with the rubber sector included the challenges posed especially by the non-tyre sector The Tier 1 companies cater to a large proportion of supply of rubber parts, hence the production lines are manage quality standards upto some extent, but they exist in small numbers and thus more such quality level suppliers and manufacturers are required.